Sovereignty Experiments Korean Migrants and the Building of Borders in Northeast Asia, 1860-1945 - Park, Alyssa M. (Cornell University Press, 2019)
Sovereignty Experiments tells the story of how authorities in Korea, Russia, China, and Japan—through diplomatic negotiations, border regulations, legal categorization of subjects and aliens, and cultural policies—competed to control Korean migrants as they suddenly moved abroad by the thousands in the late nineteenth century. Alyssa M. Park argues that Korean migrants were essential to the process of establishing sovereignty across four states because they tested the limits of state power over territory and people in a borderland where authority had been long asserted but not necessarily enforced. Traveling from place to place, Koreans compelled statesmen to take notice of their movement and to experiment with various policies to govern it. Ultimately, states' efforts culminated in drastic measures, including the complete removal of Koreans on the Soviet side. As Park demonstrates, what resulted was the stark border regime that still stands between North Korea, Russia, and China today.Skillfully employing a rich base of archival sources from across the region, Sovereignty Experiments sets forth a new approach to the transnational history of Northeast Asia. By focusing on mobility and governance, Park illuminates why this critical intersection of Asia was contested, divided, and later reimagined as parts of distinct nations and empires. The result is a fresh interpretation of migration, identity, and state making at the crossroads of East Asia and Russia
Description based on online resource; title from PDF title page (publisher's Web site, viewed 20. Jun 2019)
Keywords: Geschichte 1860-1945; HISTORY / Asia / Korea; Borderlands -- East Asia -- History; Borderlands -- Korea -- History; Borderlands -- Russia (Federation) -- Russian Far East -- History; Koreans -- East Asia -- History; Koreans -- Russia (Federation) -- Russian Far East -- History; Grenze; Souveränität; Koreaner; Migration; Tumen-Gebiet